PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA SOKA MINIMARKET BADUNG - Gede Galantika; Made Ika Prastyadewi; I Nyoman Resa Adhika (VALUES, 2023)
Employee performance is a result achieved by someone in carrying out their duties in accordance with the responsibilities given by the organization. If employee performance is getting better in a company, the higher the profit that will be obtained so that the company is required to improve employee performance so that company goals can be archived. The performance of human resources can be influenced by vorious factors, including transformational leadership, motivation and work discipline. This study aims to determine the partial effect of transformational leadership, motivation dan work discipline on employee performance at Soka Minimarket Badung. This reaserch was conducted at Soka Minimarket Badung with a population of 30 employees. The sample in this study used the cencus method where all employees were used as respondents. The data used in this study are quantitative data and primary data with data collection methods using the quenstionnaire method. The data analysis technique used is multiple linear regression analysis, determination analysis, and t test. The results showed that partially the variables of transformational leadership, motivation and work discipline had a positive and significant effect on employee performance at Soka Minimarket Badung. This means that the better the transformational leadership and the increased work motivation and discipline, the employee’s performance will also increase.